2001
DOI: 10.1002/jrs.713
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond transient resonance Raman study on the excited‐state conformational dynamics of a highly ruffled nickel porphyrin

Abstract: Picosecond to nanosecond transient resonance Raman spectroscopy was applied to track down the excitedstate conformational excursions of Ni II T(t-Bu)P [nickel(II) 5,10,15,20-tetra-tert-butylporphyrin] in various solvents with different dielectric properties. From the resonance Raman spectra of Ni II T(t-Bu)P obtained by picosecond pulse photoexcitation, the a 4 -type conformer was suggested to be dominant in the 1 (d,d) excited state at the initial stage of deactivation processes (∼3 ps). However, only one con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This state has a 3d electronic configuration of (3d x2-y2 ) 1 (3d z2 ) 1 and is here denoted T(d,d) (Figure 1). 41,47 A pump-pump-probe transient absorption measurement of Ni(II) porphyrin excited state dynamics suggested that a transient Ni(I) charge transfer state may exist with a lifetime of a few picoseconds, 40 but previously such a reaction pathway could not be substantiated by monitoring the temporal evolution of the nickel electronic configuration. In comparison to these previous optical and vibrational spectroscopic studies, X-ray transient absorption (XTA) spectroscopy, 22,23 which combines a laser excitation and conventional X-ray absorption spectroscopy, 48 can directly probe the metal center electronic structure and local geometry rather than relying on the indirect deduction of excited state dynamics from relatively broad transient optical spectral features.…”
Section: Introductionmentioning
confidence: 99%
“…This state has a 3d electronic configuration of (3d x2-y2 ) 1 (3d z2 ) 1 and is here denoted T(d,d) (Figure 1). 41,47 A pump-pump-probe transient absorption measurement of Ni(II) porphyrin excited state dynamics suggested that a transient Ni(I) charge transfer state may exist with a lifetime of a few picoseconds, 40 but previously such a reaction pathway could not be substantiated by monitoring the temporal evolution of the nickel electronic configuration. In comparison to these previous optical and vibrational spectroscopic studies, X-ray transient absorption (XTA) spectroscopy, 22,23 which combines a laser excitation and conventional X-ray absorption spectroscopy, 48 can directly probe the metal center electronic structure and local geometry rather than relying on the indirect deduction of excited state dynamics from relatively broad transient optical spectral features.…”
Section: Introductionmentioning
confidence: 99%
“…The metalloporphyrin chosen in our study was Ni(II) tetramesitylporphyrin (NiTMP). Molecular dynamics and structures of nickel(II) porphyrins were extensively studied by ultrafast transient absorption spectroscopy, [4][5][6][7][8][9][10][11] resonance Raman spectroscopy, [12][13][14][15][16][17][18][19][20] X-ray transient absorption spectroscopy [21][22][23][24][25] and quantum mechanical calculations. [25][26][27][28][29] Together, these studies showed severe non-planar distortions of the porphyrin macrocycle due to a mismatch of the smaller Ni(II) ion with the larger porphyrin macrocycle to which the Ni(II) was coordinated.…”
Section: Introductionmentioning
confidence: 99%
“…One metalloporphyrin studied by XTA was Ni(II) tetramesitylporphyrin (NiTMP), whose analogs were previously investigated by ultrafast TA [29][30][31][32][33][34][35][36], resonance Raman spectroscopy [37][38][39][40][41][42][43][44][45], previous XTA measurements [18,[46][47][48][49] and quantum mechanical calculations [49][50][51][52][53] due to their rich photochemical reaction pathways which can be used to understand similar processes in other metalloporphyrins (Fig. 1).…”
Section: Photoinduced and Ground State Ligation Of Metalloporphyrins:mentioning
confidence: 99%